Wastage of medications supplied by hospitals to facilitate continuity of care when patients are discharged to residential care facilities in Victoria, Australia: An observational study. (2nd March 2021) - Elliott, Rohan A.; Tran, Tim; Taylor, Simone E.
Abstract: Objectives: To explore wastage of hospital‐supplied medications for patients discharged to residential care facilities (RCFs). Methods: Telephone interviews with staff at 52 RCFs and nine community pharmacies after patients were discharged from three hospitals in metropolitan Victoria, Australia, with medication supplied in original packs. Results: Hospital‐supplied medication was used by most RCFs, for a median of 48 hours, while waiting for community pharmacies to deliver medications packed in the RCFs' preferred dose administration aid system (unit‐dose or multi‐dose blister packs or sachets). All RCFs reported sending unused hospital‐supplied medications to their community pharmacy. Six of the nine community pharmacies (managing 83% patients) indicated they did not reuse hospital‐supplied medications, with the exception of select difficult‐to‐source medications. Conclusion: There was significant wastage of hospital‐supplied discharge medications. Changes to the way hospital discharge medications are funded and quantities supplied are needed to ensure continuity of medication administration while minimising financial and environmental impacts of medication wastage.